India and the struggle for Indonesian independence - Ghoshal, Baladas (Universiti Kebangsaan Malaysia, 1999)
A few countries stood by Indonesia in her struggle for freedom from the Dutch. India was one them. It had made a valuable contribution to the cause of Indonesia’s independence not only through diplomatic support both inside and outside the United Nations, but also through active material support. In the United Nations, India together with Australia condemned the brutal attempt of the Dutch to recover its colonial possession in Indonesia after the Japanese surrender, and played a decisive role in mobilising the support of UN members as well as international public opinion in favour of Indonesia’s freedom. At the time when some Indonesian Republic leaders were under threat of their lives due to Dutch military action, India sent a plane under great risk to airlift them to safety in Singapore and India to enable them travel to other parts of the world to publicise their cause for freedom. India supported the Republican diplomatic representative and his mission in Delhi with financial and other help, including the facilities for broadcasting Indonesian viewpoint on the struggle for independence. As a protest to the Dutch military action against the Republican government, India stopped all KLM flights over its territory. It also sent a medical mission along with large supplies of medicine to help the victims of Dutch aggression. Parallel with the Government of India, its people expressed their solidarity with the Indonesian people through organisation of public demonstrations, refusal to deal with anything Dutch and through many other acts of moral support.